Assessing Model of Financial Satisfaction Predictors: the Mediating Effect of Financial Risk Tolerance and Financial Behavior - Yuliani Yuliani; Taufik Taufik; Mukhtaruddin Mukhtaruddin; Nyimas Dewi Murnila Saputri (Journal of Accounting Research, Organization and Economics, 2021)
Objective – This study aims to prove empirically about the prediction of financial satisfaction models based on financial knowledge and socio-economic factors of finance by taking into account financial risk tolerance and financial behavior. Design/methodology – The primary data source in the form of a questionnaire and non-probability purposive sampling technique were used with 107 responses collected during July-August 2020. The unit of analysis was an individual, namely the people in Palembang City in the age range of 20-55 years. Data analysis comprise of descriptive statistics index number method and inferential statistics SEM method by converting ordinal data into intervals. Results – It was found that direct financial knowledge, socio-economic financial had not significant on financial risk tolerance. Financial knowledge, socio economic financial significantly and positively influence financial behavior. Furthermore, direct financial knowledge, socio-economic financial, financial risk tolerance, financial behavior had a significant positive effect on financial satisfaction. The indirect effect found that finance risk tolerance is not a mediation of the influence of financial knowledge and socio-economic financial on financial satisfaction. The indirect effect of financial behavior on the influence of financial knowledge and financial socio-economic were significant. Limitation/Suggestion – This study implies that the role of financial behavior as a partial mediation on the relationship between financial knowledge and financial satisfaction. The role of perfect mediation itself is for socio-economic financial relationships and financial satisfaction.